A Descriptive Study of Thailand’s ESP Programs: Policy Implications for AEC - Sinhaneti, Kantatip (Journal of Education and Vocational Research, 2015)
As a country member, Thailand needs to prepare for the upcoming AEC. One way to look at how the country has prepared for this is to look at the ESP programs offered in universities, both public and private, especially ESP programs in preparation for the eight careers: engineering, hospitality & tourism, architecture, dentistry, medical practices, accounting, surveying, nursing. This study therefore explores the AEC careers offered in public and private universities. This was a descriptive study. The international programs under study fell into two levels: Bachelor (335 programs) and Master (436 programs). The results of descriptive analysis revealed these findings. On the eight AEC careers, three most popular programs offered in Thailand included hospitality & tourism, engineering and accounting respectively. On the other hand, no land surveying programs are offered at both levels; no dentistry programs at Bachelor level; no medical practice is offered at Master level. For policy implication, Thailand should offer these programs in the future.